Model Elektronik Word of Mouth: Citra Destinasi, Kepuasan dan Loyalitas Wisatawan - Muhammad Ras Muis; Dedek Kurniawan Gultom; Jufrizen Jufrizen; Muhammad Elfi Azhar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
This study aims to analyze the effect of e-WOM on destination image, tourist satisfaction, and tourist loyalty. Analyze the influence of destination image on tourist satisfaction and loyalty, and analyze the effect of satisfaction on tourist loyalty. This research approach is an associative approach. The location of this study was conducted in the tourist destination of the Lake Toba Region in North Sumatra. The population in this study is domestic tourists. This population was chosen, because theoretically and empirically it has various characteristics that are appropriate to the topic and purpose of the study. While the sample size is 145 tourists. Data collection techniques are a list of questions and interviews. The analytical method used in this study is the Structural Equation Model with data processing using the Lisrel 8.0 computer program. The results showed that E-WOM affected Destination Image, Tourist Satisfaction, and Tourist Loyalty, Destination Image influenced Tourist Satisfaction and Tourist Loyalty and Tourist Satisfaction influenced Tourist Loyalty.